Grassland afforestation: towards an integrative perspective of its ecological oportunities and costs - Jobbagy Gampel, Esteban Gabriel (2022)
The establishment of tree plantations on native grasslands is expanding in Argentina and Uruguay, promoted by public incentives and, likely, by an emerging market of carbon sequestration. We assessed how this transformation affects the production of ecosystem goods and services, synthesizing preexisting and original information on their influence on biomass production, water dynamics, and nutrient cycling. Field and satellite measurements show that, compared to grasslands, tree plantations in Uruguay, Entre Ríos, and Corrientes had higher primary productivity. This productivity increase was accompanied by higher evapotranspiration rates and a lower water yield, responsible of halving stream flow in afforested watersheds in Córdoba and Uruguay, in agreement with observations on 26 afforested grasslands around the world. In Buenos Aires, where phreatic water is close to the surface, trees used groundwater increasing the salinity of deep soil and the water table. Most of the tree plantations in the region acidified soils and in some cases stream water, mainly as a result of their high calcium consumption. It is urgent to generate information about other impacts of tree plantations such as changes in fire dynamics or invasive species. An integrative understanding of the influence of tree plantations on the production of goods and services will help to development new forestry systems and policies that are more sustainable and useful for society.